Enzymes Activity Study Of Multiple Types Of Iraqi Honey (Journal of Pharmaceutical Negative Results, 2022)
This study was carried out on samples of honey that represented most of the governorates of Iraq from different plant sources andincluded the following: The protein content study of the different honey varieties was studied and it was noted that there were significantdifferences at the p<0.05 level in the percentages of protein. It was noted that the protein percentage ranged between 0.14-0.73% andthe highest percentage was in the sample H12 and the lowest In the sample H15.The results of tests to determine the values of the enzyme activity of honey enzymes (diastase, invertase and glucose-oxidase) showedthat there were significant differences for these values between types of honey, as the highest value of diastase in sample H12 was 21unit and the lowest value reached 8 units in samples H4 and H8, in While the highest activity of invertase was recorded in the H7sample which amounted to 284.3 U/kg and the lowest activity in the H11 sample, which amounted to 107.5 U/kg, while the activity ofglucose-oxidase was the highest in the H12 sample amounting to 133.5 micrograms H2O2/g/h and the least effective in the H11 samplereaching 72.2 micrograms H2O2/g/h